2012
DOI: 10.2140/pjm.2012.257.53
|View full text |Cite
|
Sign up to set email alerts
|

Presentations for the higher-dimensional Thompson groupsnV

Abstract: has introduced the higher-dimensional Thompson groups nV that are generalizations to the Thompson group V of self-homeomorphisms of the Cantor set and found a finite set of generators and relations in the case n = 2. We show how to generalize his construction to obtain a finite presentation for every positive integer n. As a corollary, we obtain another proof that the groups nV are simple (first proved by Brin).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 7 publications
0
46
0
Order By: Relevance
“…Proof. We can prove this proposition exactly in the same way as [6] and [19], using k(d)-ary trees instead of binary trees.…”
Section: Clearly One Hasmentioning
confidence: 84%
See 1 more Smart Citation
“…Proof. We can prove this proposition exactly in the same way as [6] and [19], using k(d)-ary trees instead of binary trees.…”
Section: Clearly One Hasmentioning
confidence: 84%
“…As mentioned in Remark 5.13, the topological full group of G [2] × G [2] is the two dimensional Thompson group 2V 2,1 . Presentations of the group 2V 2,1 was given by M. G. Brin [6], and later it was extended to nV 2,1 by J. Hennig and F. Matucci [19]. We have to generalize some arguments of these works to…”
Section: Abelianizationmentioning
confidence: 99%
“…They were first defined by Matt Brin in [7], and can be viewed as higher-dimensional generalizations of the group V (= 1V ) defined by Richard J. Thompson (see [10] for an introduction to Thompson's groups). The groups nV are finitely presented [19] and simple [9], and for 1 ≤ j < k it is known that jV embeds into kV [7], but also that jV and kV are not isomorphic [3].…”
Section: Introductionmentioning
confidence: 99%
“…These groups are usually termed higher-dimensional Thompson's groups or Brin-Thompson groups. All of the groups sV are known to be finitely presented [HM12], and Kochloukova, Martínez-Pérez, and Nucinkis [KMPN10] showed that 2V and 3V are of type F ∞ . We prove that this result extends to all dimensions.…”
mentioning
confidence: 99%